2005
DOI: 10.1021/jp052394s
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of a Surface Stabilized Monolayer Phase of Nickel Oxide on Pd(100)

Abstract: A surface stabilized monolayer phase of nickel oxide, c(4 x 2)-Ni(3)O(4), has been found to grow epitaxially under reactive deposition conditions on Pd(100), in the presence of other adsorbed phases and in competition with them. High-quality scanning tunneling microscopy data are reported and discussed, including a detailed analysis of the defects and of the border morphology of this new phase. The data are discussed in the light of ab initio simulations of the electronic, energetic, and geometric properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 26 publications
14
52
0
Order By: Relevance
“…More importantly, the oxide nanostructures have monolayer thickness (Figure S1b), similar to NiO nanostructures grown on Pt(111) 66 and Pd(100). 67 It should be noted that, under the same deposition conditions, 3D NiO islands were obtained on the HOPG surface ( Figure S4). Therefore, it can be concluded that the interface confinement effect between oxide overlayers and metal substrates also plays a critical role in stabilization of the 2D NiO nanoislands.…”
Section: ' Introductionmentioning
confidence: 67%
“…More importantly, the oxide nanostructures have monolayer thickness (Figure S1b), similar to NiO nanostructures grown on Pt(111) 66 and Pd(100). 67 It should be noted that, under the same deposition conditions, 3D NiO islands were obtained on the HOPG surface ( Figure S4). Therefore, it can be concluded that the interface confinement effect between oxide overlayers and metal substrates also plays a critical role in stabilization of the 2D NiO nanoislands.…”
Section: ' Introductionmentioning
confidence: 67%
“…[1][2][3][4] Films of a few atomic layers may exhibit structures that are completely different from those of bulk oxides and display many different phases, depending on the growth conditions. [5][6][7][8] In some cases, even though the structural and electronic properties of the ultra-thin films are similar to those of the massive material, the films may indeed display unexpected properties. For instance, it has been shown that MgO thin films on Mo(100) or Ag(100) substrates may exhibit modified reactivity towards adsorbed molecules or metals.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions a flat continuous layer of c(4 · 2)-NiO x is formed with very few vacancy islands. For a detailed description of this surface we refer to our previous work [34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…We have reported previously the structure and morphology of NiO/Pd(1 0 0) ultrathin films, with particular attention towards novel structures and properties stemming from the large lattice mismatch [33][34][35][36][37]. In the monolayer (ML) coverage range a new defective NiO x c(4 · 2) structure (x = 1.33) has been thoroughly investigated by both static and dynamic low energy electron diffraction (LEED) [36], STM [37], and photoemission spectroscopy (both valence and core levels) [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation